2011
DOI: 10.1681/asn.2011050519
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Risk Assessment of APOL1 on Renal Disease

Abstract: Case-control studies suggest that African Americans with genetic variants in both copies of APOL1 have increased risk for hypertension-attributable ESRD and focal segmental glomerulosclerosis. Here, we tested these risk variants in the Dallas Heart Study to ascertain the prevalence of APOL1-associated renal disease in a large population-based study and to estimate the contribution of APOL1 risk variants to disparities in renal disease. We determined the genotype of 1825 African Americans and 1042 European Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
189
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(206 citation statements)
references
References 27 publications
11
189
2
Order By: Relevance
“…Our observations that black persons without the APOL1 risk alleles remain at higher risk for albuminuria and kidney function loss compared with white individuals is also important, and consistent with a prior report. 6 While high-risk APOL1 may explain about 10% of the excess incidence of albuminuria among black participants, incident albuminuria among low-risk black persons accounted for the highest proportion of albuminuria cases among black persons. We showed that race differences between low-risk black and white participants were mostly explained by adjustment for traditional risk factors such as obesity, smoking, diabetes and BP levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observations that black persons without the APOL1 risk alleles remain at higher risk for albuminuria and kidney function loss compared with white individuals is also important, and consistent with a prior report. 6 While high-risk APOL1 may explain about 10% of the excess incidence of albuminuria among black participants, incident albuminuria among low-risk black persons accounted for the highest proportion of albuminuria cases among black persons. We showed that race differences between low-risk black and white participants were mostly explained by adjustment for traditional risk factors such as obesity, smoking, diabetes and BP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Two variants in the gene encoding apolipoprotein L1 (APOL1) (termed G1 and G2), which are common among individuals with African ancestry, but very rare in Caucasian persons, are linked to ESRD and CKD. [6][7][8][9][10] The presence of two of these APOL1 variants was significantly associated with increased progression of CKD in studies that included black persons selected for established disease. 11 In one recent report, the association of APOL1 with incident CKD in middle-aged black persons appeared to be weaker than that reported for advanced disease.…”
mentioning
confidence: 99%
“…7 Among nondiabetic African Americans carrying two APOL1 nephropathy alleles, a nearly three-fold increase in risk of microalbuminuria and four-fold increase in risk of CKD (eGFR ,60 ml/min per 1.73 m 2 ) were observed. Freedman et al extended this work in a study of asymptomatic first-degree relatives of African American patients with nondiabetic forms of ESRD.…”
mentioning
confidence: 99%
“…APOL1 gene variants are also strongly associated with CKD in African Americans, including hypertensive nephrosclerosis, focal segmental glomerulosclerosis, and human immunodeficiency virus nephropathy [11,12]. Understanding the mechanisms for these associations is an intense area of investigation.…”
Section: Apolipoprotein L1 Nephropathymentioning
confidence: 99%